If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24n + 20 = 3n Reorder the terms: 20 + 24n = 3n Solving 20 + 24n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 20 + 24n + -3n = 3n + -3n Combine like terms: 24n + -3n = 21n 20 + 21n = 3n + -3n Combine like terms: 3n + -3n = 0 20 + 21n = 0 Add '-20' to each side of the equation. 20 + -20 + 21n = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 21n = 0 + -20 21n = 0 + -20 Combine like terms: 0 + -20 = -20 21n = -20 Divide each side by '21'. n = -0.9523809524 Simplifying n = -0.9523809524
| 6(-5x-1)=84 | | 18(-7x-3)+4= | | 6x-12=4x+68 | | 4n-12=3-2n | | 14-12(13-19p)= | | 3x+15=3x(x+5) | | 10a-3m=22 | | 9n-3n=2n+8 | | 10+9(6q+4)= | | 2-(2.27)= | | 3n+15=n-15 | | 22-5(6v-1)=-7 | | -18p+13+15-3p= | | 81+x-6=5 | | 5(-2n-4)=-80 | | -3p^3+p^2+3p+1=0 | | 2-2.27= | | -2=.25x+2 | | -2.5x^2-7.1x+2.2=3.7 | | [3/4a-3]=9 | | 8(-19+15y)= | | 5x+123=3x+90 | | -17(2s+10)-9s= | | 3n+9=-18 | | [-2y+6]=6 | | 2(6+3n)-4= | | 3q=7 | | 2x+3+2=5x-3 | | 4(1+4R)=84 | | K+1=-227 | | 10a+1=31 | | 5y-6=2x+3 |